John Constantine, Hellblazer : another season - Milligan, Peter; Carey, Mike, 1959- (John Constantine, Hellblazer ;, 2021)
"John Constantine's niece is out for revenge for an assault she holds him responsible for. As this second to last collection of the original John Constantine, Hellblazer series begins, Gemma Masters, John's niece, is out for revenge for an assault she holds him responsible for-but in her quest for vengeance, she summons a demon she can't control. Then, she auctions off his beloved trenchcoat to the highest occult bidder, but the garment has powers of its own, and wherever it goes, it leaves a trail of death and madness in its wake."--